YORUBA RELIGIOUS CARVING. Pagan and Christian Sculpture in Nigeria and Dahomey, by KEVIN CARROLL. Foreword by WILLIAM FAGG, GEOFFREY CHAPMAN. 172 pp. £4 10s. - Carroll, Kevin; Fagg, William; Chapman, Geoffrey (International Library of African Music, 1966)
pages: 75
Keywords: Sculpture; Yoruba (African people); African Music; Nigeria; Dahomey; Yoruba Art